Multi-Ethnic and Hinduism in Afghanistan (Al-Adyan: Journal of Religious Studies, 2021)
Although the Taliban group is well known, it is not the only representation of ethnic and religious groups in Afghanistan. Besides being inhabited by various groups from internal Islam, there are also Hindus and Sikhs. This paper aims to describe the condition of ethno-religious diversity in Afghanistan, especially regarding Hinduism. We write this article by conducting a literature study that emphasizes descriptive analysis after comparing sources from previous writings. This is obtained based on literature study with descriptive and qualitative methods. From the literature review and previous experience received from the Taliban firsthand, during the Taliban rule from 1996 to late 2001, Hindus are forced to wear yellow armbands in public to identify themselves as non-Muslims. Hindus are forced to wear the burqa, which allegedly "protects" them from harassment. This is part of the Taliban's plan to separate "non-Islamic" and "infidel" communities from Muslim communities. Even so, most ethnic and religious groups, including Hindus, refuse to leave Afghanistan because they feel less pressured by different treatment from the Taliban in the past.Meskipun kelompok Taliban terkenal, itu bukan satu-satunya representasi kelompok etnis dan agama di Afghanistan. Selain dihuni oleh berbagai golongan dari internal Islam, juga terdapat umat Hindu dan Sikh. Tulisan ini bertujuan untuk mendeskripsikan kondisi keragaman suku-agama di Afghanistan, khususnya mengenai agama Hindu. Kami menulis artikel ini dengan melakukan studi kepustakaan yang menekankan pada analisis deskriptif setelah membandingkan sumber-sumber dari tulisan-tulisan sebelumnya. Hal ini diperoleh berdasarkan studi kepustakaan dengan metode deskriptif dan kualitatif. Dari tinjauan literatur dan pengalaman sebelumnya yang diterima dari Taliban secara langsung, selama pemerintahan Taliban dari tahun 1996 hingga akhir 2001, umat Hindu dipaksa untuk mengenakan ban lengan kuning di depan umum untuk mengidentifikasi diri mereka sebagai non-Muslim. Umat Hindu dipaksa mengenakan burqa, yang diduga "melindungi" mereka dari pelecehan. Ini adalah bagian dari rencana Taliban untuk memisahkan komunitas "non-Islam" dan "kafir" dari komunitas Muslim. Meski begitu, sebagian besar kelompok etnis dan agama, termasuk Hindu, menolak meninggalkan Afghanistan karena merasa tidak terlalu tertekan dengan perlakuan berbeda dari Taliban di masa lalu.